S45 Invasive EEG investigation of insular cortex epilepsy. Issue 9 (September 2017) - Bourdillon, Pierre; Guénot, Marc; Isnard, Jean
Abstract : Introduction: The possible involvement of the insular cortex in the constitution of the epileptogenic zone can sometimes be suspected thanks to pre-surgical phase 1 non-invasive investigations. Electrophysiological abnormalities largely consist of indirect signs, and the suspected diagnosis relies on the clinical description of seizures and on metabolic imaging. This is due to the deepness of the insular cortex and this explains why invasive phase II investigations are necessary in most cases. Invasive pre-surgical investigations are based on, either Subdural Grid Electrodes (SGE), or Stereo-ElectroEncephaloGraphy (SEEG). Methods: We systematically reviewed the literature about phase II insular investigation. Results: In addition to a significantly lower complication rate, when compared to SGE, SEEG appears to be more suitable to explore a deep structure like insula. SGE offers a good electrophysiological sampling of the superficial cortex but cannot accurately investigate, neither the deep parts of the sulci, nor the cortex of the insula itself. Conversely, SEEG allows direct and precise investigation of the insula. Trans-opercular trajectories allow to reach almost any part of the insula, while recording the operculum at the same time. Last, SEEG makes it possible to perform SEEG-guided radiofrequency thermo-coagulations. Discussion: The anatomical proximity of the sylvian vessels requires to use a robust stereotactic methodology for SEEG: namely a frame-based procedure associated with X-ray vascular investigation. Moreover, SEEG may offer a therapeutic option when resective surgery, for any reason, is not feasible. Conclusion: SEEG with trans-sylvian trajectory is the most appropriate technique for intracranial insular investigation.